Compaction-driven convection in the growing inner core: research letter - Lim, Kang Wei; Deguen, R.; Cébron, D.; Schulze, Amelie; Mandea, Mioara (Geophysical research letters, 2024)
The Earth's inner core (IC) is known to exhibit heterogeneous structures with their origins still unknown. From the onset of nucleation, the IC can grow via sedimentation and compaction of iron crystals freezing out from the fluid outer core. Previous studies of IC growth have shown entrapment of fluid within the solid matrix, and unstable density profiles in 1D can appear depending on the efficiency of fluid percolation. In this study, we perform simulations of IC growth in spherical geometries (assuming axisymmetry). We find that it is possible for the IC to develop large-scale convective flows under certain conditions and, in some instances, produce small-scale heterogeneites close to the IC boundary. Assuming representative values for the physical properties of the Earth's IC, we show that it is possible for the IC to exhibit compaction-driven convection today.